The Effect of Hospital Commitment, Trust, and Communication on Supplier Satisfaction in Supply Chain Management - Ayu Laili Rahmiyati; Susilo Wulan; Elsa Primasari (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Hospital supply chains face increasing complexity, requiring strategic supplier relationships beyond transactional interactions. Despite their critical importance, supplier satisfaction remains underexplored in healthcare logistics literature. This study investigates how hospital commitment, trust, and communication influence supplier satisfaction in healthcare supply chain contexts, adopting a supplier-centric perspective. A quantitative cross-sectional survey was conducted at Hospital X Bandung, Indonesia, achieving complete census participation from 60 suppliers across six product categories. Path analysis examined relationships among commitment (9 items), trusth(4 items), communication (11 items), and supplier satisfaction (6 items) using validated 7-point Likert scales. The model explained 62% of supplier satisfaction variance (R²=0.620, F=30.422, p<0.001). Commitment exerted the strongest total effect (24.4%), followed by trust (19.7%) and communication (17.9%). All path coefficients achieved statistical significance (p<0.05). Descriptively, trust performed best (M=5.30), while communication showed critical deficiencies (M=4.02), particularly in supplier site visits (M=1.85) and strategic information sharing. Relational factors significantly influence supplier satisfaction in hospital supply chains. Hospitals should operationalize commitment through consistent behaviors, build trust via transparency, and enhance strategic communication beyond transactional exchanges. These relationship investments may yield improved supply chain resilience, preferential resource allocation.